Review of calculation methods, procedures for registration and re-registration of producer prices of medicines in the countries of the Eurasian Economic Union - A. A. Leshkevich; D. S. Yurochkin; Z. M. Golant; I. A. Narkevich (IRBIS LLC, 2020)
Aim. To analyze the methods of the state regulation of prices for the manufacturers of pharmaceutical drugs in the Eurasian Economic Community counties (EAEC).Materials and Methods. The comparison of the aspects of the price regulation was presented as short characteristics of the regulating impact of the key normative legal acts (NLA) in the sphere of price formation on pharmaceutical drugs in the EAEC. The study included the following stages: the analysis of NLA in the Russian Federation, Republic of Belarus, Republic of Kazakhstan, Republic of Moldova, Republic of Armenia, and the Kyrgyz Republic, the comparison of the list of reference countries, and decreasing coefficients.Results. The authors revealed the differences in the procedure of the registration, re-registration, referencing of prices, and decreasing coefficients for the generics. The authors highlighted the drawbacks of the existing procedure of the registration of prices in Russia in terms of the formation of the list of the referent countries, the re-registration of drugs with an increase in price, and limited economic efficiency.Conclusion. The performed analysis showed that the differences in the methods of the state regulation of prices on pharmaceutical drugs in the EAEC countries do not allow for the formation of a unified approach. However, the creation of supranational method of price formation is an essential condition for the functioning of the united market of pharmaceutical drugs.